Integrating ESG principles into corporate governance: A strategic and regulatory perspective - Miller, Katharina (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The integration of environmental, social, and governance (ESG) principles into corporate governance has evolved from a niche concern to a fundamental business strategy. This paper examines the critical role of governance structures in embedding ESG considerations into corporate decision-making. The study aims to assess existing regulatory frameworks, highlight the challenges companies face in ESG adoption, and evaluate best practices that drive sustainable corporate governance. Using a comprehensive literature review and case-based analysis, this research identifies the effectiveness of board-level oversight, the role of supervisory bodies, and the impact of emerging regulations. Findings indicate that robust governance mechanisms enhance ESG integration, yet companies continue to struggle with inconsistent reporting standards, regulatory fragmentation, and balancing stakeholder interests. These insights contribute to the ongoing discourse on sustainable business practices and corporate accountability.